Glee. The complete fourth season [videorecording (DVD)]. - Lynch, Jane, 1960-; Monteith, Cory, 1982-2013; Michele, Lea (Twentieth Century Fox Home Entertainment, 2013)
Season four of the exhilarating Emmy-winning series finds Rachel and Kurt in New York City, Finn with a surprising new career, Will and Emma at a crossroads and Sue confronting a shocking situation! Meanwhile, tension mounts as the kids in New Directions head for Regionals, facing new challenges.